2021
DOI: 10.3390/vaccines9121422
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immune Response following SARS-CoV-2 Vaccination in Liver Transplant Recipients

Abstract: As COVID-19 remains an issue in transplantation medicine, a successful vaccination can prevent infections and life-threatening courses. The probability of poor immune response in liver transplant recipients gained attention and insecurity among those patients, leading us to investigate the humoral immune response alongside the influence of underlying diseases and immunosuppressive regimen on seroconversion rates. We included 118 patients undergoing anti-spike-protein-IgG testing at least 21 days after complete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 30 publications
0
46
0
6
Order By: Relevance
“…In their study, patients were not classified according to antibody levels, even though it is now known that poor responders to vaccination are at risk of severe COVID‐19 disease. 10 To our knowledge, there is no prospective study evaluating the MMF discontinuation before vaccination on the humoral response in LT recipients. Previously, the link between MMF and more severe COVID disease has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, patients were not classified according to antibody levels, even though it is now known that poor responders to vaccination are at risk of severe COVID‐19 disease. 10 To our knowledge, there is no prospective study evaluating the MMF discontinuation before vaccination on the humoral response in LT recipients. Previously, the link between MMF and more severe COVID disease has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, MMF was a strong modifiable risk factor for a lack of vaccine response (OR 0.458, 95%CI 0.258–0.813; p = .008), consistent with previous studies of heterogeneous SOT groups. 21 , 22 Recently, Timmermann et al reported vaccine responses in 118 liver transplant patients after two doses, of whom 92 developed anti‐spike protein IgG antibodies (78%), 10 with alcohol‐induced cirrhosis and MMF risk factors for a failure to develop antibodies after vaccination. In their study, patients were not classified according to antibody levels, even though it is now known that poor responders to vaccination are at risk of severe COVID‐19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…After the second vaccine dose, only one serological non-responder was found (0.3%). In the literature, non-responders are described in patients with immune deficiencies [ 38 , 39 , 40 ]. We found no study that investigated non-responders in HW.…”
Section: Discussionmentioning
confidence: 99%
“…Three other prospective studies confirmed the poor antibody responses in patients with cirrhosis and even greater hyporesponsiveness in LT recipients ( 72 , 100 , 101 ). A study by Thuluvath et al ( 100 ) reported that 22.8% of patients with cirrhosis and 61.3% of LT recipients exhibited poor antibody responses after receiving two doses of mRNA vaccines or a single dose of the Johnson & Johnson vaccine.…”
Section: Novel Perspectives Of Covid-19 Vaccines In Patients With Cld...mentioning
confidence: 74%
“…Three other prospective studies confirmed the poor antibody responses in patients with cirrhosis and even greater hyporesponsiveness in LT recipients (72,100,101). A study by Thuluvath et al (100) (74).…”
Section: Studies On Hmi and CMI In Patients With Cld And Lt Recipientsmentioning
confidence: 84%